A new concept for tuning design weights in survey sampling : jackknifing in theory and practice /: jackknifing in theory and practice. ([2016]) - Singh, Sarjinder, 1963-; Sedory, Stephen A; Rueda, Maria Del Mar; Arcos, Antonio; Arnab, Raghunath
No abstract available